Comparative Results of “Epi-Off” Conventional versus “Epi-Off” Accelerated Cross-Linking Procedure at 5-year Follow-Up - Cristina Ariadna Nicula; Dorin Nicula; Anca Maria Rednik; Adriana Elena Bulboacă (Journal of Ophthalmology)
Purpose. The aim of our study was to compare the long-term efficacy and safety of “epi-off” conventional and “epi-off” accelerated corneal cross-linking (CXL) in patients with progressive keratoconus. Methods. “Epithelial-off” (“Epi-off”) CXL using the conventional technique (3 mW/cm2, 30 minutes) was performed in 93 eyes of 93 patients (S-CXL group) and “epi-off” accelerated method (9 mW/cm2, 10 minutes) in 76 eyes of 76 patients with progressive KCN (A-CXL group). Cases with different stages of keratoconus and topographic evidence of progression were included. Main outcomes comprised refraction, keratometry measurements, uncorrected (UCVA) and best-corrected visual acuity (BCVA), and topographical indices. Micromorphological analysis was assessed by anterior segment ocular coherence tomography (AS-OCT). The follow-up period was 5 years. Results. In both groups, Kflat presented similar results: decrease at 1 year (p=0.465), at 2 years (p=0.672), at 3 years (p=0.198), at 4 years (p=0.32), and at 5 years (p=0.864). In both groups, Ksteep presented a similar decrease at 1 year (p=0.709), at 2 years (p=0.455), at 3 years (p=0.43), at 4 years (p=0.57), and at 5 years (p=0.494), with no statistically significant difference. Decrease in Kavg was similar in both groups at all analyzed time points (p=0.18 at 1 year, p=0.093 at 2 years, p=0.57 at 3 years, p=0.154 at 4 years, and p=0.247 at 5 years). Kmax had a similar decrease in both groups at 1 year (p=0.06), at 2 years (p=0.09), at 3 years (p=0.126), at 4 years (p=0.113), and at 5 years (p=0.114). There was no statistically significant difference between the cylinder decrease in both groups (p=0.349 at 1 year, p=0.6782 at 2 years, p=0.299 at 3 years, p=0.0943 at 4 years, and p=0.144 at 5 years). The BCVA values were statistically significantly higher than the preoperative values in both groups at all time points (p<0.05). Topographical indices such as thinnest corneal point (TP), corneal volume (CV), index vertical asymmetry (IVA), index of vertical asymmetry (ISV), index of height asymmetry (IHA), index of height decentration (IHD), Belin/Ambrosio Enhanced Ectasia Display (BAD_D), and Ambrosio retinal thickness (ART Max) were significantly statistically decreased compared with baseline at all time points, in both groups. Conclusion. “Epi-off” accelerated and conventional CXL have the same efficacy in terms of improvement in visual and topographic outcomes.